The Questions of High School Students with Learning Disabilities About Attending College - Bouck, Christine L. Barker (East Carolina University, 2009)
Students with learning disabilities currently comprise the largest number of students with disabilities in the public schools. Despite this, very few of them go on to attend a four-year postsecondary institution. Because the numbers of students with learning disabilities in both the public schools and colleges are increasing, it is important to research effective methods of support for this population. However, in the past there has been little research done in this area. The purpose of this study was to examine the questions about college asked by high school students with learning disabilities of current college students with learning disabilities. Junior-level high school students in college preparatory curriculum assistance classes were asked to participate in this study. The questions asked by these high school students helped demonstrate the need for more direct transition support and education prior to high school graduation. The information gathered from this study can be used by high school and college personnel working with students with learning disabilities to develop curriculums and transition materials to help facilitate this change.
Keywords: Education, Special; Learning disabilities; College attendance--United States; Students with disabilities--United States; College students with disabilities--United States; Learning disabled teenagers--Education--United States; Curriculum planning--United States